2019
DOI: 10.3390/toxics7020024
|View full text |Cite
|
Sign up to set email alerts
|

A Neurodevelopmental Model of Combined Pyrethroid and Chronic Stress Exposure

Abstract: Attention-deficit hyperactivity disorder (ADHD) is one of the most common neurodevelopmental disorders of childhood and previous studies indicate the dopamine system plays a major role in ADHD pathogenesis. Two environmental exposures independently associated with dopaminergic dysfunction and ADHD risk include exposure to deltamethrin, a pyrethroid insecticide, and chronic stress. We hypothesized that combined neurodevelopmental exposure to both deltamethrin and corticosterone (CORT), the major stress hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 128 publications
(156 reference statements)
0
8
0
Order By: Relevance
“…To follow up on these correlational findings in humans, mouse models of pyrethroid exposure have been developed 11,[17][18][19][20][21][22][23][24] . These models have established that exposure in mice to the pyrethroid deltamethrin during pregnancy and lactation at doses well below the EPA benchmark dose of 14.5 mg/kg is sufficient to cause broad male-biased changes in the brain and behavior of the resulting offspring.…”
Section: Introductionmentioning
confidence: 99%
“…To follow up on these correlational findings in humans, mouse models of pyrethroid exposure have been developed 11,[17][18][19][20][21][22][23][24] . These models have established that exposure in mice to the pyrethroid deltamethrin during pregnancy and lactation at doses well below the EPA benchmark dose of 14.5 mg/kg is sufficient to cause broad male-biased changes in the brain and behavior of the resulting offspring.…”
Section: Introductionmentioning
confidence: 99%
“… 23 , 24 Pyrethroids and neonicotinoids have high affinity to the soils with potential to bioaccumulate in the environment, but in humans are neurotoxins associated with poor development and neurological disorders. 25 - 27 …”
Section: Introductionmentioning
confidence: 99%
“…23,24 Pyrethroids and neonicotinoids have high affinity to the soils with potential to bioaccumulate in the environment, but in humans are neurotoxins associated with poor development and neurological disorders. [25][26][27] Quantifying pesticide residues in Ugandan foods can improve understanding of human exposure to pesticides in Uganda, providing evidence to inform policies intended to protect Uganda's community while at the same time supporting healthy food production practices. The very few studies that have examined pesticide residues in Ugandan produce have focussed on dithiocarbamate (Mancozeb) and organochlorines in tomatoes and carrots and reported levels that were above the Codex Alimentarius MRLs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, just a few animal studies on Alzheimer's disease have reported on utilization of FSCV so far [161,162]. Similarly, there are few explorations of the role of DAT in attention deficit hyperactivity disorder-related animal models [135,163,164].…”
Section: Discussionmentioning
confidence: 99%